The reemergence of whooping cough in the 21st century. Literature review and update - Auza-Santiváñez, Jhossmar Cristians; Colque-Mollo, Ruben Omar; Jiménez-Fernández, Roberto Carlos; Ortega Martinez, Rommer Alex; Viruez-Soto, Antonio; Gutiérrez-Beltrán, Joel (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Whooping cough (pertussis) caused by Bordetella pertussis is a highly contagious respiratory tract infection. continues to be a global public health problem. The World Health Organization reported 151,074 cases of pertussis worldwide and estimated 89 000 deaths in 2018. In recent years, pertussis epidemics have been observed in countries that have maintained high vaccination coverage. According to the official report of the Ministry of Health and Sports, the total accumulated cases of Coqueluche in Bolivia reach 756, of which 469 are up to 5 years old and 287 older than that age range and 8 deaths had to be regretted until August 10, 2023. Coqueluche is a notifiable disease. It is important to reflect that infectious diseases have no borders; a relevant question would be whether Bolivia is prepared or is failing to control this outbreak of reemerging disease, after COVID-19. We should not lower our guard or dismiss early action; new preventive strategies are needed.